Bone Morphogenetic Protein Signaling Is Required for Aortic Valve Calcification. Issue 7 (July 2016) - Gomez-Stallons, M. Victoria; Wirrig-Schwendeman, Elaine E.; Hassel, Keira R.; Conway, Simon J.; Yutzey, Katherine E.
Abstract : Objective—: Calcific aortic valve disease (CAVD) is the most prevalent type of heart valve disease, affecting ≈2% of the US population. CAVD is characterized by the presence of calcific nodules, resulting in aortic valve (AoV) stenosis; however, the underlying mechanisms driving disease remain unknown. Studies of human diseased AoV provide initial evidence that bone morphogenetic protein (BMP) signaling, essential for normal bone formation, is activated during CAVD. Mice deficient in Klotho, an FGF23 transmembrane coreceptor, exhibit premature aging and develop AoV calcific nodules as occurs in human CAVD. The role of BMP signaling in the development of CAVD was examined in porcine aortic valve interstitial cells (VICs) and Klotho −/− mice. Approach and Results—: We show that activation of BMP signaling, as indicated by pSmad1/5/8 expression, precedes and later localizes with AoV calcification in Klotho −/− mice. In addition, cellular and extracellular matrix changes resembling features of normal bone formation are accompanied by increased osteochondrogenic gene induction in calcified Klotho −/− AoV. Likewise, osteogenic media treatment of porcine VICs results in BMP pathway activation, increased osteochondrogenic gene induction, and formation of calcific nodules in vitro. We demonstrate that genetic inactivation of the BMP type IA receptor in Klotho −/− aortic VICs, as well as BMP pathway inhibition of osteogenic media–treated aortic VICs in vitro, results in the inhibition of AoV calcification. Conclusions—: BMP signaling and osteochondrogenic gene induction are active in calcified Klotho −/− AoV in vivo and calcified porcine aortic VICs in vitro. Importantly, BMP signaling is required for the development of AoV calcification in vitro and in vivo. Abstract : Supplemental Digital Content is available in the text.